Software engineering for resilient systems : 9th International Workshop, SERENE 2017, Geneva, Switzerland, September 4-5, 2017, Proceedings /: 9th International Workshop, SERENE 2017, Geneva, Switzerland, September 4-5, 2017, Proceedings. (2017) - Unknown
No abstract available